The Afrikaans version of the Juvenile Arthritis Multidimensional Assessment Report (JAMAR) - Scott, Christiaan; Okong’o, Lawrence; Brice, Nicky; Murless, Sarah; Slamang, Waheba; Fadlelmola, Abubaker; Consolaro, Alessandro; Bovis, Francesca; Ruperto, Nicolino (Rheumatology international, 2018)
The Juvenile Arthritis Multidimensional Assessment Report (JAMAR) is a new parent/patient reported outcome measure that enables a thorough assessment of the disease status in children with juvenile idiopathic arthritis (JIA). We report the results of the cross-cultural adaptation and validation of the parent and patient versions of the JAMAR in the Afrikaans language. The reading comprehension of the questionnaire was tested in ten JIA parents and patients. Each participating centre was asked to collect demographic, clinical data and the JAMAR in 100 consecutive JIA patients or all consecutive patients seen in a 6-month period and to administer the JAMAR to 100 healthy children and their parents. The statistical validation phase explored descriptive statistics and the psychometric issues of the JAMAR: the three Likert assumptions, floor/ceiling effects, internal consistency, Cronbach’s alpha, interscale correlations, test–retest reliability, and construct validity (convergent and discriminant validity). A total of 91 JIA patients (4.4% systemic JIA, 35.1% oligoarticular, 23.1% RF negative polyarthritis, 37.4% other categories), and 98 healthy children were enrolled in one paediatric rheumatology centre. The JAMAR components discriminated well healthy subjects from JIA patients. All JAMAR components revealed satisfactory psychometric performances. In conclusion, the Afrikaans version of the JAMAR is a valid tool for the assessment of children with JIA and is suitable for use both in routine clinical practice and in clinical research.